A community-based cross-sectional study to explore awareness about various components of mother and child protection card among mothers utilizing Village Health and Nutrition Day services - Rafique, Farhat; Arya, Anupama; Yadav, Shiv Kumar (International Journal Of Community Medicine And Public Health, 2025)
Background: The mother and child protection card (MCP Card) is a card designed to provide essential health services and benefits to mothers and their children. It serves as a tangible reminder of their rights to healthcare and encourages active participation in maternal and child health programs. Concerted efforts are needed at various levels to promote awareness and utilization of the MCP card. Methods: A community-based cross-sectional study was conducted in the rural and urban field practice area of the Community Medicine Department. 46 mothers having children up to the age of 2 years were enrolled by a convenient sampling method, and a semi-structured closed-ended questionnaire was used for data collection. Results: >70% of the respondents knew about details regarding ANM, AWW, and ASHA workers in their area. 50% of mothers were aware about detailed mentioned on card about health programs related to mother and child care, vaccines during pregnancy, pregnancy care and danger signs, important developmental milestones of the baby, and danger signs of developmental delay etc. 30% of respondents had awareness related to knowledge about investigations during pregnancy and after delivery, newborn care and danger signs, symptoms and treatment of diarrheal and pneumonia diseases, and awareness about different contraceptive methods available at government facilities. Only 10% of respondents had awareness about IFA supplementation and albendazole track record on the MCP card. Conclusions: Efforts are required at the community level to improve understanding and utilization of the MCP card.